THE EFFECTIVITY OF BELIMBING WULUH FRUIT ETHANOLIC EXTRACT ON DECREASING 2-HOUR POST PRANDIAL BLOOD GLUCOSE LEVELS OF DIABETIC MALE RATS - Devy Octarina; M Kamaluddin; Theodorus - (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Diabetes mellitus is a chronic metabolic disorder characterized by blood glucose levels greater than normal - hyperglycemia (fasting blood glucose ? 126 mg / dl or post prandial blood glucose ? 200 mg / dl or blood glucose ? 200 mg / dl) caused by insulin deficiency and or insulin resistance. One way to control blood glucose levels can be done in a traditional way using natural ingredients. Belimbing wuluh fruits (Averrhoa bilimbi Lin.) has been widely used by the community because containing many active substances, including flavonoids. Flavonoids found in Belimbing wuluh fruit are dihydromyricetin. The purpose of this study was to assess the effectivity of belimbing wuluh fruit ethanolic extract on decreasing 2-hour post prandial blood glucose of male rats compared to acarbose. This type of study is in vivo laboratory experimental (pre and posttest only). The research was done from July to September 2020 in the Biochemistry Laboratory, Biotechnology Laboratory and Animal House, Faculty of Medicine, Sriwijaya University, Palembang. The population of study were white male rats. Statistical data analysis used SPSS version 22. Based on the results of the study, it was concluded that the ethanolic extract of belimbing wuluh fruit (Averrhoa bilimbi Linn.) was effective on decreasing 2-hour post prandial blood glucose levels of diabetic male white rats.